The Explo’Santé mixed methods protocol: an interventional research school health promotion project in France - Matteo Olivo; Adeline Darlington-Bernard; Corélie Salque; Laurie Fraticelli; Emmanuel Ricard; Florence Carrouel; Emily Darlington (Archives of Public Health)
Abstract Background According to WHO, “noncommunicable diseases (NCDs) kill 41 million people” annually, as the primary cause of death globally. WHO’s Global Action Plan for the prevention and control of NCDs 2013–2020 (extended) tackles this issue and its implications regarding inequalities between countries and populations. Based on combined behavioural, environmental and policy approaches, health promotion aims to reduce health inequities and address health determinants through 3 strategies: education, prevention and protection. It is a well-known fact that long-term efficiency in health promotion, that is to say the promotion of health and well-being, involves interventions and programmes which target / involve children [1]. As a focal point in communities and a key environment for children, school is an important setting to implement health promotion programmes, especially integrated approaches and interventions targeting Life Skills (LS). Indeed, LS contribute to health and well-being, particularly for pupils. This article presents the research protocol of a French integrated school-based health promotion interventional research programme which intends to support the health promoting schools (HPS) approach in France: Explo’Santé. It results from a partnership between the University of Lyon and the French League against Cancer. Methods Explo’Santé is an observational study based on a mixed methods research design, which aims to evaluate the effects of a health promotion programme, to elicit its implementation process and identify contextual factors. This 3-year, complex programme targets primary school pupils aged 8 to 10. It incorporates health education sessions, to develop pupils’ LS and health literacy (HL), and to promote healthy environments. Teachers and French League prevention officers are trained to support skill development and programme sustainability. Data collection includes quantitative data via questionnaires, to assess programme impact on approximately 700 pupils, as well as 36 teachers, and 6 prevention officers, as well as qualitative data collected via focus groups with pupils, and interviews with teachers, parents, prevention officers, and school heads, to understand the barriers and promoting factors to the implementation of the programme, the differences in process and effects in different contexts, and its potential for sustainability. Discussion Explo’Santé was designed to contribute to school-based health promotion strategies, by including key players, promoting partnerships, targeting multiple levels of impact and effect, and to ensure every step is research-based and informed. Finally, this study aims to identify the elements which would enable Explo’Santé to become a model in France and internationally.